Reconstruction of The Definition of An Advocate in The Criminal Justice System based on Certain Qualification Standards - Hamka Ferynando; Natsir Asnawi (Asian Journal of Social and Humanities, 2026)
Amendments to the regulations in Law Number 20 of 2025 concerning the Criminal Procedure Code raise fundamental issues regarding the definition of an advocate, particularly as formulated in Article 1, number 22, which expands the scope of legal service providers beyond professional advocates. This expansion creates a dualism between advocates, who are a profession with specific qualification standards, and non-professionals who are allowed to provide legal services. This situation creates disharmony with Law Number 18 of 2003 concerning Advocates. It has implications for legal uncertainty, degradation of professionalism, and the potential weakening of the protection of suspects' rights in the criminal justice system. This study aims to analyze the normative weaknesses in the definition of an advocate and to formulate a legal reconstruction that guarantees the certainty of qualification standards. The method used is a normative juridical approach, with statutory and conceptual analysis, as well as qualitative analysis through legal interpretation. The research findings indicate that expanding the definition of an advocate without clear qualifications risks obscuring the legitimacy of the advocacy profession as an officium nobile and weakening its function as a counterweight to state power. Legal reconstruction is needed through reaffirming advocacy as a qualification-based profession, strictly separating it from non-advocate legal aid providers, and harmonizing the provisions in the New Criminal Procedure Code (KUHAP) with the Advocates Law. This approach is expected to maintain a balance between access to legal aid and ensuring the quality of defense, thereby realizing a just and integrity-based criminal justice system.